The Diffusion of an Administrative Innovation - Teece, David J. (Management Science, 1980)
This paper examines the diffusion of a particular kind of multidivisional administrative structure—the “M-Form”—in two classes of large industrial firms. The M-Form organization is a multidivisional structure with quasi-independent divisions which are assigned profit center standing and which are monitored and guided by a headquarters organization. A simple deterministic model commonly employed to represent the diffusion of technological innovations is utilized to explain the diffusion of the M-Form structure. The commendable performance of the model suggests that additional insights from the study of technological innovation can be applied with advantage to the study of administrative innovation.